2016
DOI: 10.1111/cge.12739
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted nitric oxide signaling due to GUCY1A3 mutations increases risk for moyamoya disease, achalasia and hypertension

Abstract: Moyamoya disease (MMD) is a progressive vasculopathy characterized by occlusion of the terminal portion of the internal carotid arteries and its branches, and the formation of compensatory moyamoya collateral vessels. Homozygous mutations in GUCY1A3 have been reported as a cause of MMD and achalasia. Probands (n = 96) from unrelated families underwent sequencing of GUCY1A3. Functional studies were performed to confirm the pathogenicity of identified GUCY1A3 variants. Two affected individuals from unrelated fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…It was later shown by site-directed mutagenesis that SNO-αC516 is involved in desensitization of sGC to NO stimulation in cells treated with stress-induced angiotensin II [8]. A recent study also identified in two different families that mutation αC516 to a Tyrosine as an increased risk for the Moyamoya disease (vasculopathy), achalasia and hypertension [23]. A specific role for the three other Cys in the catalytic domain αC609, αC628 and βC571, identified as S-nitrosated in the current study, is not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…It was later shown by site-directed mutagenesis that SNO-αC516 is involved in desensitization of sGC to NO stimulation in cells treated with stress-induced angiotensin II [8]. A recent study also identified in two different families that mutation αC516 to a Tyrosine as an increased risk for the Moyamoya disease (vasculopathy), achalasia and hypertension [23]. A specific role for the three other Cys in the catalytic domain αC609, αC628 and βC571, identified as S-nitrosated in the current study, is not yet known.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological role of the solvent exposed, potentially reactive Cys in sGC, still needs to be addressed. Interestingly, a recent study described an increased risk for Moyamoya disease (vasculopathy), achalasia, and hypertension linked to mutation of aC517 to tyrosine (109). Many questions regarding the potential roles of Cys remain unanswered, including the role of the PDI-sGC association.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, variants in GUCY1A3 have also been associated with blood pressure [16], an important cardiovascular risk factor [18]. Additionally, mutations in GUCY1A3 have also been found in patients suffering from Moyamoya syndrome, a rare progressive cerebrovascular disorder [14,29].…”
Section: Discussionmentioning
confidence: 99%